Sleep quality, daytime sleepiness and daytime functioning among Thai obstructive sleep apnea patients receiving continuous positive airway pressure therapy - Theerakorn Theerakittikul; Jindarat Chaiard; Jirawan Deeluea (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose is to assess the effectiveness of continuous positive airway pressure (CPAP) treatment on sleep quality, daytime sleepiness and daytime functioning among Thai obstructive sleep apnea (OSA) patients. Design/methodology/approach - A repeated measures clinical intervention design was implemented. Participants were 50 patients first time diagnosed with OSA and prescribed CPAP treatment. The intervention composed of CPAP health education, and follow-up evaluation. Data on CPAP adherence were downloaded from Smartcards of the CPAP device. The Thai PSQI, ESS and FSAQ-10 questionnaires were administered at baseline, 1-month, and 3-months. Descriptive statistics and repeated measure analysis with multilevel mixed-effects modeling approach were used. Findings - Thirty-nine participants completed the study. Approximately 53% (n = 25) and 71.1% (n = 27) of the patients adhered to CPAP treatment by the end of the 1- and 3-months, respectively. After controlling for patients' adherence, at 1-month follow-up, the intervention improved quality of sleep (β = −2.65, 95% CI = −1.60, −4.13), daytime functioning (β = 3.24, 95% CI = 1.87, 4.61) and decreased daytime sleepiness (β = −3.29, 95% CI = −1.85, −4.73). At 3 months, the intervention still improved quality of sleep (β = −3.53, 95% CI = −2.05, −5.01), and daytime functioning (β = 4.34, 95% CI = 2.76, 5.92), and decreased daytime sleepiness (β = −4.82, 95% CI = −3.16, −6.49). Originality/value - Adherence to CPAP treatment is effective in improving sleep quality, daytime functioning and reducing daytime sleepiness. Patient-oriented strategies for enhancing CPAP adherence should be developed and implemented as a standard care in sleep clinics.